2009
DOI: 10.1007/s00429-008-0200-6
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxic lesions of the thalamic reuniens or mediodorsal nucleus in rats affect non-mnemonic aspects of watermaze learning

Abstract: Rats with bilateral neurotoxic reuniens (RE), mediodorsal (MD), hippocampal (HIPP) or sham (SH) lesions were tested in a standard watermaze task, together with unoperated rats. RE-rats and SH-controls readily learned to swim directly to a hidden platform. In contrast, MD-rats displayed a transient deficit characterized initially by thigmotaxis. Like in previous studies, HIPP-rats had long latencies throughout training and displayed more random swims than the other groups. In a memory probe test with the platfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 70 publications
8
71
1
3
Order By: Relevance
“…Our results showing no effect of the ReRh lesion on recent memory retention appear contradictory. However, the results of Dolleman-van der Weel et al (2009) show that the rats with ReRh lesions performed above chance level, and thus remembered the platform location. Another study assessed reference and working memory performance in a water maze after ReRh inactivation, but conclusions were unclear as controls did not remember the platform location (Davoodi et al, 2009).…”
Section: The Ventral Midline Thalamus and Memorymentioning
confidence: 89%
See 2 more Smart Citations
“…Our results showing no effect of the ReRh lesion on recent memory retention appear contradictory. However, the results of Dolleman-van der Weel et al (2009) show that the rats with ReRh lesions performed above chance level, and thus remembered the platform location. Another study assessed reference and working memory performance in a water maze after ReRh inactivation, but conclusions were unclear as controls did not remember the platform location (Davoodi et al, 2009).…”
Section: The Ventral Midline Thalamus and Memorymentioning
confidence: 89%
“…Considering the key position of the ReRh nuclei at the interface between the hippocampus and the mPFC (Hoover and Vertes, 2012), the relatively small number of studies that paid attention to their functional implications remains surprising. Dolleman-van der Weel et al (2009) showed in rats that Re lesions did not prevent water-maze acquisition, but impaired performance in a delayed (24 h) probe trial. This impairment was attributed to a too rapid shift of strategy after an initial search oriented toward the correct quadrant, possibly as a consequence of maladaptations to envi- Figure 8.…”
Section: The Ventral Midline Thalamus and Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of behavioural studies has provided evidence that RE is indeed involved in cognitive functions, most likely by coordinating neuronal activities in hippocampus and mPFC (Dolleman-van der Weel et al, 2009;Davoodi et al 2011;Eleore et al 2011;Hembrook et al 2011;Loureiro et al 2012;Prasad et al 2012;Cholvin et al 2013;Hallock et al 2013;Xu and SƱdhof 2013;Saalmann 2014;Bobal and Savage 2015;Ito et al 2015;Layfield et al 2015;Prasad et al 2016). Because mPFC lacks a direct return projection to the hippocampus (Sesack et al 1989;Jay and Witter 1991), RE might relay mPFC-processed information back to the hippocampus as part of a closed CA1-mPFC-RE-CA1 circuit Xu and SƱdhof 2013).…”
Section: Functional Relevancementioning
confidence: 99%
“…Other midline thalamic lesions that include the Re have been shown to impair certain aspects of memory function, especially as it relates to the flexible control of navigation strategies (Dolleman-van der Weel et al, 2009;Cholvin et al, 2013) but fail to disrupt working memory (Chudasama and Prasad, 2012). Recently, Xu and SĂŒdhof (2013), using optogenetic methods, showed that the Re outputs to the prefrontal cortex, and prefrontal inputs to the Re enable rats to respond quickly and appropriately to fearful situations.…”
Section: Cognitive Effects Of Disrupting Thalamic Relaysmentioning
confidence: 99%